The Age Friendly Supermarket Index: a Delphi study and psychometric analysis - Sok Leng Che; Wai In Lei; Sok Man Leong (Frontiers in Public Health, 2026)
Background and objectives Person–environment interactions shape how individuals evaluate their surroundings, and perceived age friendliness influences intentions to age in place. Supermarkets, as essential components of daily urban life, play a critical role in supporting older adults’ community participation. This study aimed to develop and validate the Age Friendly Supermarket Index (AFSI), a comprehensive tool to assess and enhance supermarket age friendliness for older customers. Methods Indicators were generated through a literature review, followed by two Delphi rounds, cognitive interviews, and pilot testing. The AFSI was validated using survey data from 387 older adults in Macao. Results The finalized AFSI includes 33 indicators across three domains: (i) environmental design and customer service, (ii) convenience and safety assurance, and (iii) product arrangement and aisle planning. Exploratory and confirmatory factor analyses supported a three factor structure. The overall index showed excellent internal consistency (Cronbach’s α = 0.93), with strong reliability across domains (α = 0.90–0.92), explaining 54.96% of variance. Measurement invariance was confirmed across gender, age groups, and living status. Conclusion The AFSI is a reliable and valid instrument for evaluating supermarket age friendliness and can guide improvements to support age-friendly shopping environments.